Does “Dr. Google” improve discussion and decisions in small animal practice? Dog and cat owners use of internet resources to find medical information about their pets in three European countries - Springer, Svenja; Lund, Thomas Bøker; Corr, Sandra A.; Sandøe, Peter (Frontiers in Veterinary Science, 2024)
Modern dog and cat owners increasingly use internet resources to obtain information on pet health issues. While access to online information can improve owners' knowledge of patient care and inform conversations with their veterinarian during consultations, there is also a risk that owners will misinterpret online information or gain a false impression of current standards in veterinary medicine. This in turn can cause problems or tensions, for example if the owner delays consulting their veterinarian about necessary treatment, or questions the veterinarian's medical advice. Based on an online questionnaire aimed at dog and cat owners in Austria, Denmark and the UK (N=2117) we investigated the use of internet resources to find veterinary medical information, the type of internet resources that were used, and whether owner beliefs explain how often they used the internet to find medical information about their pet. Approximately one in three owners reported that they never used internet resources prior to (31.7%) or after (37.0%) a consultation with their veterinarian. However, when owners do make use of the internet, our results show that they were more likely to use it before than after the consultation. The most common internet resources used by owners were practice websites (35.0%), veterinary association websites (24.0%), or 'other' websites providing veterinary information (55.2%). Owners who believe that the use of internet resources enables them to have a more informed discussion with their veterinarians more often use internet resources prior to a consultation, whereas owners who believed that internet resources help them to make the right decision for their animal more often use internet resources after a consultation. The results suggest that veterinarians should actively ask pet owners if they use internet resources, and what resources they use, in order to facilitate open discussion about information obtained from the internet. Given that more than a third of pet owners use practice websites, the findings also suggest that veterinarians should actively curate their own websites where they can post information that they consider accurate and trustworthy.